Chiliaditi Syndrome - Gurbuz, Sukru; Yildiz, Mustafa; Bozdemir, Mehmet Nuri; Kilicaslan, Isa; Atescelik, Metin; Ayranci, Mehmet; Onur, Ruhi (Aves, 2011)
Chiliaditi syndrome is an unusual disease usually resulted from interposition of colon, hepatic flexura or intestines to the space between liver and diaphragma. Diagnosis is usually incidental based on the chest or abdominal radiographies.
Keywords: Chiliaditi syndrome; emergency; diaphragm